The Dynamics Of Religious Tolerance In The Academic Environment Of Higher Education Institutions In Banjarmasin - Husna, Nur; Erlina; Satria Buana, Mirza; Erniyati, Tiya; Sari, Septiana; Yani, Risyda; Winanda, Dilla (AL-ADYAN, 2025)
Lecturers, as educators and role models, play a strategic role in internalizing the values of religious tolerance within the academic environment. Higher education institutions function as multicultural and multireligious spaces, making it essential to ensure that these values are effectively implemented in teaching practices and interpersonal interactions on higher education. This study aims to identify best practices employed by lecturers in fostering an inclusive learning atmosphere for students from diverse religious backgrounds. The research applied a qualitative approach, with data collected through observation, interviews, and literature review, conducted at Lambung Mangkurat University and the Islamic University of Kalimantan (UNISKA). The findings indicate that religious tolerance in both universities develops more significantly through practical implementation in academic culture, lecturers' professional ethics, and daily interactions within the university community, rather than through formal regulations. The fairness demonstrated by lecturers and the diversity among students constitute important social capital for cultivating an inclusive academic environment. Despite challenges such as the potential for sensitive religious jokes, differing interpretations, and the influence of external socio-political issues, continuous reinforcement through character education, interfaith dialogue, and institutional commitment is necessary to ensure that tolerance is not only preserved but also strengthened as a model of multicultural education to be emulated by other universities.   Keywords: Religious Tolerance; Dynamics; Academic Environment; Higher Education